2020
DOI: 10.22492/ije.8.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Learner-Centered English Language Teaching: Premises, Practices, and Prospects

Abstract: Although learner-centered education is claimed to have several learning gains, research suggests that teachers' attitudes and practices play a crucial role in promoting its prolific outcomes. This study examines the adaptation of learner-centered education and examines how it has been implemented in second language teaching by university teachers since launching an educational shift embodied in the learner-centered reform a decade ago. In so doing, a questionnaire was distributed to a random sample of 128 inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…According to Figure 7, it can be seen that the I/O performance will decline with the increase of time. The best I/O performance of reference [6] model and reference [7] model is only at the beginning of the system operation, which will directly lead to the poor degree of video streaming, The number of services available is too small, but the number of services in this model continues to increase in the first five minutes, and remains above 6000 even if it decreases later. This is because this model includes a portal and a streaming video server.…”
Section: Analysis Of Experimental Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…According to Figure 7, it can be seen that the I/O performance will decline with the increase of time. The best I/O performance of reference [6] model and reference [7] model is only at the beginning of the system operation, which will directly lead to the poor degree of video streaming, The number of services available is too small, but the number of services in this model continues to increase in the first five minutes, and remains above 6000 even if it decreases later. This is because this model includes a portal and a streaming video server.…”
Section: Analysis Of Experimental Resultsmentioning
confidence: 98%
“…. In order to verify the overall effectiveness of the proposed method, it is necessary to test the I/O performance and peak signal-to-noise ratio of the multilevel input English teaching model, reference [6] model, and reference [7] model considering diversified 7: By comparing the I/O performance of different methods, we can directly reflect the advantages and disadvantages of the system, operate the system for a long time, and give the same number of instructions to the three methods. According to Figure 7, it can be seen that the I/O performance will decline with the increase of time.…”
Section: Analysis Of Experimental Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, 10.3389/feduc.2022.965659 they recommended a blended learning model to increase student performance and maintain learner engagement. Tichavsky et al's (2015) and Ritthipruek's (2018) studies both reflect some of the main ideas of learner-centered education (LCE)-the idea that teaching should focus on the individual needs of learners (Badjadi, 2020). Past research has indicated that implementing LCE methods can be challenging for instructors (e.g., Bai and González, 2019).…”
Section: Literature Review Learner-centered Online Educationmentioning
confidence: 99%